Optimizing Sharia Crowdfunding Platforms as an Instrument for Financing Free Healthcare Services: A Study on Implementation and Sustainability - Zuchroh, Imama; Maulidina, Zaidah (Science Tech Group, 2025)
This study examines the potential of Sharia-compliant crowdfunding platforms as innovative financial instruments to support free healthcare services in developing countries. Despite significant advancements in healthcare provision globally, millions remain without access to adequate care due to financial constraints, particularly in nations with large Muslim populations. This research employs a qualitative descriptive methodology with a library research approach to analyze the implementation, challenges, and sustainability factors of Sharia crowdfunding in the healthcare sector. Findings reveal that Sharia crowdfunding platforms offer promising avenues for healthcare financing through models such as donation-based (Sadaqah), reward-based, interest-free loans (Qard Hasan), and equity participation (Musharakah). The study identifies critical success factors including regulatory framework development, technological infrastructure, transparency mechanisms, stakeholder collaboration, and Sharia compliance governance. Key challenges encompass limited awareness, trust deficits, technological barriers, and sustainable funding models. The research contributes to the growing discourse on alternative healthcare financing mechanisms and provides practical recommendations for policymakers, healthcare providers, and Islamic financial institutions to optimize these platforms for expanding healthcare access while maintaining alignment with Islamic financial principles.